BUDGETARY GOAL CHARACTERISTICS DAN TRANSPARANSI SERTA PENGARUHNYA TERHADAP KINERJA ANGGARAN DAN KINERJA MANAJERIAL - Luh Komang Merawati (UNHI Press, 2019)
Budget performance and managerial performance in public sector has been public concern and much noticed by the public since they are closely related to the aspects of public accountability. Achievement of budget performance and managerial performance is determined by the level of transparency and budgetary goal characteristics which consists of indicators of budgetary participation, difficulty in budget goals, budget feedback, budget evaluation and difficulty in budget goals. This research was conducted to examine the effect of budgetary goal characteristics and transparency on budget performance and managerial performance in the Housing, Settlement and Land Agency (DPKPP) of Denpasar City, Bali Province. The data collection method used is by distributing questionnaires and obtained as many as 51 respondents as samples based on purposive sampling technique. The data analysis technique uses Partial Least Square analysis. The results showed that the budgetary goal characteristics did not affect budget performance, the budgetary goal characteristics had a positive effect on managerial performance, transparency had a positive effect on budget performance, while transparency had a negative effect on managerial performance in DPKPP Denpasar.